P080 Mucosal clock and inflammation regulatory genes are disrupted in treatment naïve pediatric patients with ulcerative colitis. (30th January 2023) - Labes, S; Tabach, Y; Matar, M; Shamir, R; Shouval, D S; Froy, O; Weintraub, Y
Abstract: Background: The human circadian clock is present in cells throughout the body. It consists of CLOCK and BMAL1 that heterodimerize and bind to E-box sequences to mediate transcription of a large number of genes, including Period s ( PERs ) and Cryptochrome s ( CRYs ). PERs and CRYs constitute part of the negative feedback loop and inhibit CLOCK:BMAL1 -mediated transcription. Recently, we have shown that patients with active ulcerative colitis (UC) display tissue-specific misalignment of the molecular clock that reverts to normal following effective treatment. Several circadian clock genes also function as anti-inflammatory regulators. RORa, PPARa and PPARg are positive regulators of the clock mechanism and induce the expression of IkB, a suppressor of NFkB. In the same manner, PCG1a induces transcription of IL10. Our aim was to characterize the expression of these regulators compared to that of core clock genes and determine their correlation in UC patients. Methods: Clock gene expression patterns using whole transcriptome RNA sequencing were retrieved from the IBD Transcriptome and Metatranscriptome Meta-Analysis platform (TaMMA IBD). We compared rectal biopsy gene expression of 12 clock genes and their isoforms ( AMPK, BMAL1, CLOCK, CRY1, CRY2, PER1, PER2, PCG1a, PPARa, PPARg, REV-ERB, RORa, RORg and SIRT1 ) in 206 treatment naïve pediatric patients with UC (age 12.9±3.2; 54% male) and 20 healthy controls (age 13.9±3.3; 45% male). Spearman correlations were calculated between all 12 clock genes within each of the UC and control cohorts. Results: Core clock genes: BMAL (p<0.0001), CLOCK (p<0.01) and CRY1 (p<0.0001), and the anti-inflammatory regulator gene RORa (p<0.0001) were upregulated in UC patients compared to controls. In contrast, expression of other anti-inflammatory regulatory genes: PCG1a (p<0.0001), PPARa (p<0.01), PPARg (p<0.0001) and RORg (p<0.0001) was decreased. Clock gene expression levels of healthy controls show discordant correlations compared to UC patients. For example, correlations between BMAL/REV-ERBa as well as PPAR g/ REV-ERB a were inverted between controls and UC patients (r=-0.44 vs . r=0.13 and r =-0.4 vs. r=0.3, respectively). Figure 1. Expression of clock and inflammation regulatory genes in UC patients vs. healthy controls. Conclusion: Core clock gene expression was disrupted, and anti-inflammatory regulator gene expression was decreased in patients with active UC vs. controls. The demonstration of discordant correlations of some positive vs. negative feedback loop genes in UC highlights the clock disruption in active inflammation. Since these clock regulators also ameliorate inflammation, their reduced expression may explain not only clock dysregulation but also increased tissue inflammation.